Productivity and Thermal Performance Enhancements of Hollow Fiber Water Gap Membrane Distillation Modules Using Helical Fiber Configuration: 3D Computational Fluid Dynamics Modeling - Elbessomy, Mohamed O.; Elsheniti, Mahmoud B.; Elsherbiny, Samy M.; Rezk, Ahmed; Elsamni, Osama A. (Membranes (Basel), 2023)
Although hollow fiber water gap membrane distillation (HF-WGMD) units offer certain advantages over other MD desalination systems, they still require enhancements in terms of distillate flux and productivity. Therefore, this work proposes a novel configuration by incorporating the helical turns of HF membranes within the water gap channel of the HF-WGMD modules. A fully coupled 3D CFD model is developed and validated to simulate the multifaceted energy conservations and diffusion mechanisms that are inherent to the transport phenomena in the proposed HF-WGMD module. Single and double helical HF membrane designs with different numbers of turns are compared to the reference modules of single and double straight HF membrane designs under various operational conditions. At a feed temperature of 70 °C, a noteworthy 11.4% enhancement in the distillate flux is observed when employing 20 helical turns, compared to the single straight HF membrane module. Furthermore, the specific productivity revealed a maximum enhancement of 46.2% when using 50 helical turns. The thermal performance of the proposed HF-WGMD module shows higher energy savings of up to 35% in specific thermal energy consumption for a one-stage module. Using three stages of single helical modules can increase the gain output ratio from 0.17 for the single stage to 0.37, which represents an increase of 117.6%. These findings indicate the high potential of the proposed approach in advancing the performance of HF-WGMD systems.